2004
DOI: 10.34101/actaagrar/15/3350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ozone Exposure on Phytopathogenic Microorganisms on Stored Apples

Abstract: The aim of our study was to clarify the effect of ozone exposure on several phytopathogenic fungi on stored apple fruits under different storage conditions. The study was conducted at Bistrita, Romania, in the storehouse of an experimental apple orchard in 2002 and 2003. Two widely grown apple cultivars (‘Jonathan’ and ‘Golden Delicious’) were used. General microbial examination of the fruits was made during storage in order to identify the most important storage pathogens. Efficacy of six ozone treatments was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…Ozone exposure decreased the disease incidence (% of fruit that show any degree of spoilage due to fungal infection) in apples treated with ozone at 25 ppm for 30–90 min, in grapes exposed to gaseous ozone at 200 ppm for 15 min or at 2500 ppm for 2 h, 5000 ppm for 1 h and 10 000 for 30 min . Similarly, decay of grapes was significantly reduced in produce continuously exposed to ozone at 100 ppb for up to 60 days, at 300 ppb over 7 weeks and in grapes continuously or intermittently (12 h per day) exposed to ozone at 2 ppm for 72 days, in tangerine exposed to gaseous ozone at 200 ppm for 4–6 h, in strawberries exposed to gaseous ozone at 1.5 ppm for 3 days, but not when the dose of ozone at 0.35 ppm for 3 days was too low to prevent decay of strawberries or in blueberries exposed to gaseous ozone at 450 ppb for 2 days .…”
Section: Ozone As An Antimicrobial Agentmentioning
confidence: 99%
“…Ozone exposure decreased the disease incidence (% of fruit that show any degree of spoilage due to fungal infection) in apples treated with ozone at 25 ppm for 30–90 min, in grapes exposed to gaseous ozone at 200 ppm for 15 min or at 2500 ppm for 2 h, 5000 ppm for 1 h and 10 000 for 30 min . Similarly, decay of grapes was significantly reduced in produce continuously exposed to ozone at 100 ppb for up to 60 days, at 300 ppb over 7 weeks and in grapes continuously or intermittently (12 h per day) exposed to ozone at 2 ppm for 72 days, in tangerine exposed to gaseous ozone at 200 ppm for 4–6 h, in strawberries exposed to gaseous ozone at 1.5 ppm for 3 days, but not when the dose of ozone at 0.35 ppm for 3 days was too low to prevent decay of strawberries or in blueberries exposed to gaseous ozone at 450 ppb for 2 days .…”
Section: Ozone As An Antimicrobial Agentmentioning
confidence: 99%
“…The high reactivity, penetrability and spontaneous decomposition to a nontoxic product (O 2 ) make ozone an alternative that enables food safety from a microbiological point of view, mainly because ozone has been classified as a GRAS (Generally Recognized as Safe) material in the United States and approved by the FDA (Food and Drug Administration) for direct contact with foods. Usually, low ozone concentrations and short contact times are needed to inactivate bacteria, fungi, yeasts, parasites and viruses, but the susceptibility of microorganisms to ozone varies, among other factors, with the physiological state of the culture, pH, temperature, humidity and the presence of additives [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…An experiment conducted by Puia and Oroian (2004) found that “Golden Delicious” apples were more resistant to storage diseases after ozone treatment. Ozone treatment was most effective when 25000 ppb ozone was applied for 0.5 or 1.5 h immediately after harvest and before storage.…”
Section: Discussionmentioning
confidence: 99%
“…Blueberries appear to be highly susceptible to fungal infection and after inoculation with B. cinerea spores, fruit rapidly developed decay at 20 • C. Another reason for the lack of ozone effect could be due to latent infection that occurred early in the growing season, and gaseous ozone is unable to penetrate the fruit tissue to kill the fungi. An experiment conducted by Puia and Oroian (2004) found that "Golden Delicious" apples were more resistant to storage diseases after ozone treatment. Ozone treatment was most effective when 25000 ppb ozone was applied for 0.5 or 1.5 h immediately after harvest and before storage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation